Когнитивный подход к формированию сценариев разрешения проблемной ситуации в хозяйственной деятельности предприятия - Лисицкий, Василий Лаврентьевич; Фонта, Н. Г. (Eastern-European Journal of Enterprise Technologies, 2009)
The article deals with the use of cognitive modeling to study specific feature of industrial firm, non precise mathematical analysis. Using the cognitive approach has allowed the technology to build a formation scenario of resolving the problem situation in the economic activities of industrial firm